Penilaian Kesejahteraan Masyarakat Untuk Mendukung Permukiman Berkelanjutan di Kelurahan Terboyo Wetan, Semarang - Sariffuddin, Sariffuddin; Susanti, Retno (Makara Human Behavior Studies in Asia, 2011)
The essence on sustainable development is to have human life quality improvement and assure their sustainability. Today, the development of city is only focused in environmental changes without deeply developing the human who dwells it. Even, such cities in Indonesia tends to follow market mechanism as also like the settlement on Terboyo Wetan sub district, district of Genuk, Semarang City. The settlement has been developed since its opening as an industrial zone of Genuk in 1980s. The settlement, initially was fishermen settlement, where the society has enlivens their life from the sea. The enormously industrialization has changed the society living condition. To explore intensively, this observation has three aims, as follows: (1) the understanding residents welfare of the society, (2) understanding residents preference toward residents welfare, and (3) understanding on capability of the society to support sustainability of the settlement. This research was using qualitative method and improving hypothesis by reality on the field. Study finding revealed that the settlement of fragile Terboyo Wetan is not in continuous form. Based on objective assessment, from 5 quality of life aspect according to human settlement understanding, there is only 1 aspect supported, which is society while the other four aspects (man, nature, shells and network) are not properly supporting. Indeed, the, which anthropocentris, created unfriendly behaviors toward their environment. It is reflected by the meaning of residents welfare according to the society as such basic need fulfillments in economics scopes instead of as vastly for environmental living aspect. Hence some of them assumed that the condition of environmental degradation is a normal consequence for terrestrial settlement.